Using Ecological Dynamics and Expert Knowledge to Explore Expertise-Appropriate Practice Pedagogies for the Taekwondo Roundhouse Kick - Bercades, Luigi Rene Titong (Auckland University of Technology, 2023)
Using a taekwondo skill, this thesis presents the application of ecological dynamics to technical coaching that may help in adapting to rapid developments in rules and technology. The thesis also demonstrates a framework for using the coaching-biomechanics interface to reveal knowledge that will benefit both coaches and researchers. The coaching-biomechanics interface seeks to integrate coaches’ experiential and researchers’ theoretical approaches to identify and solve the same problem. While the framework in this thesis builds on the literature on the coaching-biomechanics interface, it could potentially guide knowledge creation and dissemination in other fields. To this end, the research was designed with three studies that flowed into each other. First, the first study presented in Chapter 3 aimed to capture expert taekwondo coaches’ experiential knowledge of the critical variables that determine an effective roundhouse kick. Specifically, the coaches provided information on the variables they thought would contribute to scoring kicks in competition and those that would distinguish between intermediate and expert performers. The secondary aim was to evoke the coaching-biomechanics interface and translate the coaches’ knowledge into observable biomechanical variables for future investigation. The final aim was to elicit further expert knowledge to assess the usefulness of the resulting variables. The study presented in Chapter 4 examined expert-intermediate differences in the coach-identified and researcher-translated critical variables to verify their usefulness in determining expertise. Three-dimensional measurements were made on intermediate and expert participants while performing the kick in varying levels of representativeness, all of which are routinely used in taekwondo practice. To further increase representativeness, the participants kicked a live target (the author) who was wearing the competition approved body armour, and kick effectiveness was determined by the scoring average on the armour. Finally, the study presented in Chapter 5 investigated the effects of a six-week representative learning intervention in terms of the coach-identified and researcher-translated critical variables and kick effectiveness. A case-series design was used in which multiple single-subjects were observed. Comparisons were made to expert coordination from Chapter 4 with respect to variability changes in the front knee angle at cut, the front knee angle at kick, and the interpersonal distance at the cut between levels of representativeness. In Chapter 3, six higher-order themes emerged from interviews of four expert taekwondo coaches: (1) hip flexibility, (2) balance, (3) control/coordination, (4) distance, (5) footwork, and (6) speed. These were supported by several sub-themes. By using the coaching-biomechanics interface, the authors translated each theme and sub-theme into biomechanical variables based on existing research and potential usefulness to coaching: (1) front knee height, (2) support foot balance, (3) foot velocity, (4) interpersonal distance, and (5) cut-kick transition speed. Two separate expert coaches appraised these variables in terms of understanding, importance, coachability, and differences in expertise. Results shown in Chapter 4 that variability in the normalised knee angle at the cut reduced when a target was present (F (2, 18) = 6.09, p = .010, ηp2 = 0.404). Similarly, the variability in the normalised knee angle at the kick dropped considerably in the presence of a dynamic target (F (2, 18) = 4.28, p = .030, ηp2 = 0.323). Experts had greater variability than intermediates with respect in IPD at the cut (F (1, 9) = 7.386, p = .024, ηp2 = 0.451). These variables’ marginal significances and moderate effect sizes were taken as evidence of interaction and formed the basis for an expert model that may reflect responses to applied pedagogy in the following study. While no pre-post differences were found in the observed variables as part of the study presented in Chapter 5, the limited implementation of the learning intervention appeared to result in emerging expert coordination patterns in the interpersonal distance at the cut. Although the changes in coordination did not produce clear immediate or lingering post-intervention scoring improvements, elements of this study’s learning intervention could easily be adopted to coaching practice and future research. With an ecological dynamics framework, this thesis used a more representative research design to examine a model for the coaching-biomechanics interface. Taken together these studies support the use of expert coach knowledge as a device for analysis and communication between sport scientists and coaches. These conclusions are however limited by the availability of relevant expertise, which in turn left several results underpowered. Much has been learned about taekwondo from this thesis, some of which may be generalised to other combat sports. However, the author would like to highlight the coaching-biomechanics interface, the fruitful collaboration between researchers and coaches, an approach that hopefully inspires more efforts to close the gap between research and practice.